Progress Toward Increasing Women's and Minorities' Access to Top State Government Jobs?. (June 2022) - Lewis, Greg; Boyd, Jonathan; Pathak, Rahul
This study examines the impact of qualifications and hiring advantages on women's and minorities' access to state government jobs, both in managerial and high-salary positions and overall. It also looks at how race and gender differences in representation have changed since 1990 and how they compare with the private sector. All groups, except Latino and Asian men, are more likely than White men to work for state governments, and all groups are more likely to do so than comparable White men. White men remain more likely to be managers and to earn top-decile salaries than comparable White women and people of color. Differences in education, experience, veteran status, and citizenship contribute, in different ways, to each group's underrepresentation at top levels, but sizable unexplained gaps remain. The good news is that access to top jobs is better in state governments than in the private sector and has improved since 1990.